The Implementation of Criminal Sanctions on Criminal Acts of Narcotics - Ristikowati, Mei; Hanim, Lathifah (Law Development Journal, 2021)
This study aims to examine and analyze the application of criminal sanctions against perpetrators of narcotics crimes and judges' considerations in the application of sanctions to perpetrators of narcotics crimes in the Batang District Court. The research method used is a Sociological Juridical Approach. Based on the results of the research on the application of criminal sanctions against perpetrators of narcotics crimes, starting from the indictment of the public prosecutor, who charged him with the Subsidarity charge, namely Article 114 paragraph (1), Article 112 (1) and Article 127 of Act No. 35 of 2009 concerning Narcotics. The basis for the examination in court is the Indictment of the Public Prosecutor, then the Panel of Judges conducts an examination of the indictment, in order to prove whether the Defendant has committed the crime as stated in the Article charged by the public prosecutor, whether the description of the defendant's actions is correct, which will be proven based on the applicable legislation. Considering the panel of judges in their decision, the panel of judges in their examination uses the theory of proof and punishment, where in the Aquo case the panel of judges will prove the elements contained in Article 114 paragraph (1), Article 112 (1) and Article 127 of Act No. 35 of 2009 concerning Narcotics as stated in the indictment of the public prosecutor, then examine the statements of witnesses, associated with the statements of the defendant and documentary evidence so that the facts of the trial will be obtained and evidence will be obtained which are mutually compatible and mutually reinforcing, from the results the research according to the authors of the panel of judges in court examinations has been based on the theory of evidence and the theory of punishment.